Dekomposisi Faktor-Faktor Rasio Keuangan: CR, TATO, DAR dan ROA Dalam Memprediksi Pertumbuhan Laba - Fortuna, Anastasya Corry; Mudjijah, Slamet (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2024)
Research Aim: This study aims to explore the impact of Current Ratio, Total Asset Turnover, Debt To Asset Ratio, and Return On Asset on Profit Growth in Building Construction Subsector Companies listed on the Indonesia Stock Exchange for the period 2018-2022. Methods: Utilizing a quantitative approach and multiple linear regression analysis, this study leverages annual financial data from 15 construction companies listed on the IDX, analyzed with SPSS version 22. Findings: The research results indicate that the Debt To Asset Ratio and Return On Asset significantly affect Profit Growth, whereas the Current Ratio and Total Asset Turnover do not show a significant influence. Theoretical Contribution/Originality: This research contributes to the literature by highlighting the importance of debt management and asset efficiency in influencing profit growth in the construction sector, as well as providing empirical evidence from a developing market like Indonesia. Practical Implication: These findings offer insights for the management of construction companies to prioritize debt management and efficient use of assets as strategies to enhance profit. Research Limitation: This study is limited to data from construction companies listed on the IDX, hence the results may not be generalized to other sectors or geographic regions. Future research could expand the sample and consider external variables such as macroeconomic conditions.